Pendampingan Pendidikan Karakter Siswa Melalui Implementasi Moderasi Beragama di MTs Sirojul Hikmah Bojonegoro - Munir Munir; Farida Isroani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Qur'an is also believed to include this word as al-Salam (a term for Allah the Most Calm), muslim (a person who seeks a peaceful life), silm (harmony itself), Islam (a term for the religion sent by the Prophets). off lifting Allah's expression), so that humans live in harmony with themselves, their families, social networks, the grave, until they enter heaven